Concealed abnormal atrial phenotype in patients with Brugada syndrome and no history of atrial fibrillation. (15th February 2018) - Conte, Giulio; Caputo, Maria Luce; Volders, Paul G.A.; Luca, Adrian; Mainardi, Luca; Schotten, Ulrich; Corino, Valentina D.A.; Regoli, François; Zeemering, Stef; Zink, Matthias; Yazdani, Sasan; Kappenberger, Lukas; et al.
Abstract: Objectives: The electrocardiogram (ECG) of patients with BrS in sinus rhythm might reflect intrinsic atrial electrical abnormalities independent from any previous atrial fibrillation (AF). Aim of this study is to investigate the presence of P-wave abnormalities in patients with BrS and no history of AF, and to compare them with those displayed by patients with documented paroxysmal AF and by healthy subjects. Methods: Continuous 5-min 16-lead ECG recordings in sinus rhythm were obtained from 72 participants: 32 patients with a type 1 Brugada ECG, 20 patients with a history of paroxysmal AF and 20 age-matched healthy subjects. Different ECG-based features were computed on the P-wave first principal component representing the predominant morphology across leads and containing the maximal information on atrial depolarization: duration, full width half maximum (FWHM), area under the curve and number of peaks in the wave. Results: Patients with BrS and no history of AF (mean age: 53 ± 12 years; males: 28 pts., spontaneous type 1 ECG: 20 pts., SCN5A mutation: 10 pts) presented with longer P-wave duration, higher FWHM and wider area under the curve in comparison with the other two groups. Although P-wave features were abnormal in BrS patients, no significant difference was found between patients with spontaneous type 1 ECG and ajmaline-induced type 1 ECG, symptomatic and asymptomatic ones, and between patients with a pathogenic SCNA5 mutation and patients without a known gene mutation. Conclusions: Patients with BrS without previous occurrence of AF present with a concealed abnormal atrial phenotype. In these patients atrial electrical abnormalities can be detected even in the absence of an overt ECG ventricular phenotype, symptoms and a SCN5A mutation.